Analysis of Legal Basis in Education: Study of Law, Policy and Deviance in Education - Nasrul Syakur Chaniago; Refi Syahputra; M. Amri Nasution; Fahrul Sanawi; Amiruddin Siahaan; Inom Nasution (STAI Hubbulwathan Duri, 2023)
The low quality of Indonesia's human resources (HR) is caused by irregularities (non-compliance with regulations and implementation) that occur in the process of providing education. This study aims to analyze the legal basis in the field of education and its implementation in Indonesia. The formulation of the research problem includes how the foundations and policies of education in Indonesia are and how the legal position (specifically in the field of education) is in hacking educational irregularities. This study uses an approach to the literature study method in the form of Preferred Reporting Items for Systematic Review (PRISMA). A systematic literature review is systematic by collecting some relevant evidence according to specified criteria to answer several questions. The results of this study conclude that enacting laws, government regulations and regulations of the minister of education regarding the